Environment and the Social Sciences: Perspectives and Applications. 1972
DOI: 10.1037/10045-009
|View full text |Cite
|
Sign up to set email alerts
|

Bedroom size and social interaction of the psychiatric ward.

Abstract: The appropriate bedroom size in a psychiatric ward poses a question that constantly plagues designers, administrators, and physicians. Historically, solutions have ranged through almost all possible combinations. In the past, the major conflicting pressures in arriving at a solution have been costswhich dictated large, multiple-occupancy rooms-and therapeutic considerations-which argued in favor of single or small rooms. Recent developments in design and construction techniques, however, have tended to diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

1975
1975
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 0 publications
0
28
0
4
Order By: Relevance
“…One of the earliest studies conducted on indoor spaces utilized behavior mapping to show differences in social interaction between patients in single-, double- and multiple-occupancy rooms [ 6 ]. Moore used behavior mapping to study the differences in the use of the outdoors, with emphasis on differences in the outdoor behavior of girls and boys after the reconstruction of a playground [ 7 ]. The method was widely used in studying outdoor settings such as outdoor children’s museums and neighborhood parks due to its unobtrusive applicability in public spaces [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the earliest studies conducted on indoor spaces utilized behavior mapping to show differences in social interaction between patients in single-, double- and multiple-occupancy rooms [ 6 ]. Moore used behavior mapping to study the differences in the use of the outdoors, with emphasis on differences in the outdoor behavior of girls and boys after the reconstruction of a playground [ 7 ]. The method was widely used in studying outdoor settings such as outdoor children’s museums and neighborhood parks due to its unobtrusive applicability in public spaces [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review carried out in the mid-1980s indicated that the use of behavioral tables for data collection with regard to indoor settings was a popular method at that period [ 11 ]. In work on hospitals, behavioral tables were adopted instead of a plan layout [ 7 ]. Similarly, in more recent research on hospitals, behavioral tables have been preferred for recording data during observation cycles [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each of the environmental features affecting NSTs has also been shown to affect the quantity and qual-ity of informal social contact among neighbors. Crowded, high-density living conditions have been linked to social withdrawal (Baum & Valins, 1979;Ittelson, Proshansky, & Rivlin, 1970). High-crime settings are associated with neighbors staying home (Rohe & Burby, 1988) and avoiding local social contact (Conklin, 1971).…”
Section: The Role Of the Setting In The Development Of Neighborhood Smentioning
confidence: 99%
“…38 This is because patients can opt for a private space, and yet they can also often leave the room, unlike patients staying in rooms with other patients who may isolate themselves searching for privacy. 39 Other structural and design changes also influence the patients and the team, including the well-being of the users -an important outcome in health. 33,37 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%